Activation study of a 15MeV LINAC via Monte Carlo simulations. (July 2020) - Vichi, Sara; Dean, Devis; Ricci, Silvia; Zagni, Federico; Berardi, Paola; Mostacci, Domiziano
Abstract: Medical linear accelerators are increasingly used in radiotherapy. During the operational life of the accelerator, the different components of the LINAC head become radioactive due to photonuclear reactions. Activation induced has to be evaluated to assess not only the dose due to residual activation but also the amount of radioactive waste that has to be managed in the dismantling phase of the facility. The aim of this work is to define a Monte Carlo approach for the preliminary assessment of activation levels of a LINAC head. In this work the MC code FLUKA was used to simulate the Elekta Precise Treatment System 15 MeV LINAC installed in 2004 at the Bellaria Hospital (Bologna, IT) and routinely used in radiotherapy treatments. The activation of the LINAC head was assessed in each component after 15 years of operation. The main long-lived radionuclides found in head components are W-181, Re-184, Ni-63, Co-57, Fe-55, Mn-54, while short-lived radionuclides are W-187, W-185, W-179, Re-188, Re-186, Re-184, Cu-64, Cu-62, Ni-65, Ni-57, Cr-55 and Mn-56. As expected the most active component is the target while no considerable activation were found in the ionization chamber and in the wedge. Highlights: The activation induced in a LINAC head was assessed via Monte Carlo simulations. The Elekta Precise Treatment System 15 MeV LINAC was investigated. A detailed Monte Carlo model of the LINAC head was implemented using FLUKA. The main long and short lived radionuclides produced were assessed.